The effect of traditional games on students' gross motor skills, physical fitness, and social skills - M. Afif; Bafirman Bafirman; Yanuar Kiram; Masrun Masrun (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study examined the effect of a structured traditional games intervention on gross motor skills, physical fitness, and social skills among elementary students. A quantitative quasi-experimental one-group pretest–posttest design was applied to 57 fifth-grade students (aged 10–11 years) at SD Telkom Padang, Indonesia. The intervention consisted of selected traditional games conducted over six weeks (three sessions per week, 70 minutes each). Gross motor skills were measured using TGMD-2, physical fitness using the Indonesian Student Fitness Test (TKSI), and social skills using the SSRS teacher rating scale. Data were analyzed using MANOVA to examine simultaneous effects across variables. Results showed a significant multivariate effect (Pillai’s Trace = 0.415, F = 25.993, p < 0.05; η²p = 0.415). Univariate tests indicated significant improvements in gross motor skills (F = 56.959; η²p = 0.337), physical fitness (F = 41.011; η²p = 0.268), and social skills (F = 58.553; η²p = 0.343). These findings suggest that structured traditional games can support multidimensional student development in physical education.